LITHOLYTIC THERAPY AT THE TREATMENT OF CHOLELITHIASIS (REVIEW OF LITERATURE) - E. V. Razmakhnin; S. L. Lobanov; O. G. Konovalova (Acta Biomedica Scientifica, 2014)
Treatment of cholelithiasis in patients with high operative risk need requires minimally invasive methods. Contact bilestones litholysis is a perspective direction. For this purpose it is recommended to use medications with the highest litholytic activity and the lowest side effects. It is necessary to seek for an adequate concrement dissolvent because of mineral and organic composition of bilestones. The article presents comparative analysis of characteristics of various dissolving agents proceeding from effectiveness and intensity toxic effects.